The Influence of MEDULA (Education Media for Snakes and Ladders) on Adolescent Knowledge Levels on Reproductive Health - Ema Waliyanti; Anindya Sekar Utami; Evi Novitasari; Miranda Ayu Fitri Amelia; Rahmawati Rahmawati; Faudyan Eka Satria (Journal of Health Technology Assessment in Midwifery, 2021)
Adolescents have a distinctive characteristic of great curiosity to take risks without careful consideration. This makes teenagers enter susceptible to perform behaviors such as pre-marital sexual behavior which bring many negative effects, physically, psychologically, and socially. Therefore, it is required the availability of reproductive health services that are friendly and appealing to teenagers, such as a playful education by using the ladder snake games, so that the respondents catch much information is submitted. This study was tried to determine the effect of health education with the ladder snake games to students’ knowledge level about adolescent reproductive health. This quasi-experimental study used pre-posttest design with control group. The sample used was 116 students in the secondary school, selected through the total sampling method. Instruments in this study used questionnaires that its validity and reliability had been tested.  As well as ladder snakes measuring 2x2 meters. Data were analyzed by nonparametric Statistic test. Wilcoxon test showed a significance value of 0.000 (p 0.05) which means there are significant differences in the intervention group before and after health education with snake ladder. This research concluded that there was ladders snake game influence to the students’ knowledge about adolescent reproductive health.